The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/0266666915616666
|View full text |Cite
|
Sign up to set email alerts
|

The concept of Librarian 2.0 in Kuwaiti academic libraries

Abstract: Attempts have been made to explore the impact of Information Communication Technology (ICT) on the entire gamut of the library and information sector and to conceptualise the transformation of conventional libraries into Web 2.0, Library 2.0 and Librarian 2.0, which will bring a changing scenario to the information industry. In the last few years, discussion and debate about the 'core competencies' needed by Librarian 2.0 have appeared in the academic environment. This investigation aims to identify the key sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Over the past three decades, libraries have embraced marketing to improve library services and create stronger contacts with the user community (Garoufallou, Siatri, Zafeiriou and Balampanidou, 2013;Garoufallou, Zafeiriou, Siatri and Balapanidou, 2013;Siddike et al, 2015) so as to increase library use, enhance the value and image of the library, provide user education, and change user perceptions (Al-Daihani and AlAwadhi, 2015). Library 2.0, which is a model for modern library services that focuses on user-centered change and participation, has significantly changed the types of interactions between libraries and their users (Ghuloum and Buabbas, 2016). Further, as technological developments have led to the increased use of internet services, academic libraries have begun to embrace social media to better engage with various community groups outside the physical library walls to ensure that resources and services are more accessible and user friendly (Harrison et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the past three decades, libraries have embraced marketing to improve library services and create stronger contacts with the user community (Garoufallou, Siatri, Zafeiriou and Balampanidou, 2013;Garoufallou, Zafeiriou, Siatri and Balapanidou, 2013;Siddike et al, 2015) so as to increase library use, enhance the value and image of the library, provide user education, and change user perceptions (Al-Daihani and AlAwadhi, 2015). Library 2.0, which is a model for modern library services that focuses on user-centered change and participation, has significantly changed the types of interactions between libraries and their users (Ghuloum and Buabbas, 2016). Further, as technological developments have led to the increased use of internet services, academic libraries have begun to embrace social media to better engage with various community groups outside the physical library walls to ensure that resources and services are more accessible and user friendly (Harrison et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…While new technologies have added value to library services by presenting new modes of collecting, storing, retrieving and providing information, they have also brought new challenges and aggravated some of the challenges that faced libraries before (Emmanuel and Sife, 2008). Ghuloum and Ahmed (2011) have indicated that several factors such as financial factors, technological factors, human factors and cultural factors may be a barrier in ensuring utilization of ICTs. These have included such factors as a lack of sufficient funds to support the purchase of the technology, lack of qualified library professionals, lack of motivation and need among librarians to adopt ICT in their daily operations (Ani et al, 2005;Starr, 2006).…”
Section: Adequacy Of Information Materialsmentioning
confidence: 99%
“…Pwani University Library their various operations with information retrieval systems are being designed to suit the needs of end users as well as to simplify the process. The ICTs as used in academic libraries attempts to deliver numerous applications such as wide-area network applications, local area networks, online information services (the Internet), online databases, library databases, CD-ROMs, online access catalogues, retrieval networks, digital online archives, mainframe computers, microcomputer labs, and other digital content services (Ghuloum and Ahmed, 2011). With the advent of computers and telecommunications technologies, libraries and information services can now provide access to these resources through workstations such as personal computers (PCs) and terminals that are in patrons 'offices, as well as in the library building.…”
Section: Library Services User Satisfaction Atmentioning
confidence: 99%
“…One of the major search engines Alta Vista has reported in 2008 that it has indexed 60 million Web pages. By 2012 the number of Web pages indexed by this search engine has leaped to more than 100 million (Ghuloum and Ahmed, 2011). Technology has resulted in convergence of two movements in the libraries affecting information access, namely: New forms of information; and new technologies that have transformed library holdings.…”
Section: Library Services User Satisfaction Atmentioning
confidence: 99%